Undifferentiated connective tissue diseases and adverse pregnancy outcomes. An undervalued association?. (16th September 2017) - Spinillo, Arsenio; Beneventi, Fausta; Caporali, Roberto; Ramoni, Veronique; Montecucco, Carlomaurizio
Abstract : Undifferentiated connective tissue diseases (UCTDs) are a heterogeneous group of disorders characterized by symptoms and signs suggestive of systemic autoimmune rheumatic disease (ARD), but which do not fulfill all the established criteria for definite diagnosis of a condition. Although a third of UCTDs can progress to a definite ARD within months or years, most UCTDs can remain stable for years with minimal disease activity. The annual incidence of UCTD in the general population ranges from 14 to 140 per 100 000 people. UCTDs are associated with the persistence of several circulating autoantibodies including antinuclear, antiphospholipid or antithyroid antibodies. Immunological evaluation of subjects with UCTDs suggests a proinflammatory state and dysregulation of the Th1/Th2 balance. Autoantibodies have well‐known deleterious effects on placentation and have been associated with an increased risk of prematurity, fetal growth restriction (FGR), preeclampsia, and congenital atrioventricular heart block. Although epidemiological and biological data suggest a potential negative impact on reproductive outcomes, the relationship between UCTD and pregnancy outcomes has not been adequately studied. While awaiting definitive data from large studies, obstetricians should be aware that rheumatic disorders in their early, incomplete, or undifferentiated phases can adversely affect pregnancy outcomes, increasing the likelihood of pregnancy loss, FGR, preeclampsia, and prematurity.